The Problems of Ensuring the Quality of Experts’ Work: the Case of Media Content Evaluation in the Russian Federation - Yulia A. Krasheninnikova (Управленческое консультирование)
The paper deals with the problems of ensuring the quality of expert’s activities which results are used in public administration. As a case, one type of expert evaluation is examined. This type has appeared about six years ago, according to the Federal Law N 436-FZ On Protecting Children from Information Harmful to Their Health and Development, with the purpose to assess the age rating of media content in difficult or disputable cases. The research focuses on two topics: what errors and abuses happen in the practice of expert evaluations; how the procedures of quality ensuring work. Empirical data for analysis include the texts of expert evaluations over the period 2013–2017 years (N 105) and semi-structured interviews with accredited experts (N 10). It was revealed that the quality of expert evaluations is diverse and in some cases is far from satisfactory. Some evaluations can be questioned because of their noncompliance with the law and formal criteria of academic papers. Meanwhile, obvious procedures to ensure quality are not designed in the law or exist but do not actually work. The results of evaluations of similar products differ from each other because of the absence of common methods, common theoretical ground, and unified format of evaluation. The government control of the experts’ work quality and the self-regulation of expert community are very weak. Those circumstances create conditions for distorted attitude of stakeholders to expert evaluation: not as a supplement tool for enforcement of the law on children media safety but as self-sufficient instrument of private interest protection and influence on media.